Population-based analysis of the association between composite dietary antioxidant index and pediatric obesity - Zhou, Qingnv; Wu, Yuhao; Xu, Hui; Xie, Hongyu; Yang, Rongwei; Huang, Huafei (Frontiers in Nutrition, 2025)
ObjectivesPediatric obesity is an increasingly serious global problem. Although much attention has been paid to the role of nutrition in pediatric obesity, no prior study has examined the association between the composite dietary antioxidant index (CDAI), the main measure of an antioxidative diet, and pediatric obesity, and this research aims to investigate this relationship.MethodsUsing the National Health and Nutrition Examination Survey (NHANES) for the period 2009–2018, we examined the relationship between CDAI and pediatric obesity: body mass index (BMI) and waist-to-height ratio (WHtR) using multivariate linear regression models and smoothing fit curves. Furthermore, subgroup analyses were conducted to observe differences in these associations across various stratifying factors.ResultsOur study encompassed 10,019 participants aged 6–18 years with complete data. There was a significant negative correlation between CDAI and BMI (β = −0.04, 95% CI: −0.09, −0.00, p = 0.0367) and WHtR (β = −0.08, 95% CI: −0.15, −0.02, p = 0.0089). Additionally, a one-unit increase in CDAI was linked to a 1.9% decrease in the odds of obesity as defined by WHtR (OR = 0.98, 95% CI: 0.96, 1.00, p = 0.0342). Notably, the negative associations between CDAI and both BMI and WHtR varied across subgroups.ConclusionOur findings reveal a linear negative relationship between CDAI and both BMI and WHtR among American children and adolescents, offering novel insights into the potential protective role of antioxidant-rich diets against pediatric obesity.